2018
DOI: 10.1016/j.renene.2018.02.041
|View full text |Cite
|
Sign up to set email alerts
|

The role of renewable versus non-renewable energy to the level of CO2 emissions a panel analysis of sub- Saharan Africa’s Βig 10 electricity generators

Abstract: Highlights • We estimate the determinants of CO 2 emissions. • Focus on the 10 biggest electricity generators in Sub-Saharan Africa from 1980 to 2011. • A long-run relationship between the main variables is confirmed. • Increases in NRE rise CO2; while increases in RE decrease CO2. • CO2, income, trade and NRE cause RE; NRE cause CO2; while CO2 and NRE cause trade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
116
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(137 citation statements)
references
References 78 publications
21
116
0
Order By: Relevance
“…The corresponding effects in the long run are 0.528, 0549 and 0.101%. The results are in line with those of most studies in the literature such as Shahbaz et al[20], Farhani et al[27], Heidari et al[15], Inglesi-Lotz and Dogan[44] who find that energy consumption increases environmental degradation.Our result is attributed to the fact that the Algerian, Egyptian and South African economies are primarily based on the exploitation and the exports of fossil ener-…”
supporting
confidence: 92%
“…The corresponding effects in the long run are 0.528, 0549 and 0.101%. The results are in line with those of most studies in the literature such as Shahbaz et al[20], Farhani et al[27], Heidari et al[15], Inglesi-Lotz and Dogan[44] who find that energy consumption increases environmental degradation.Our result is attributed to the fact that the Algerian, Egyptian and South African economies are primarily based on the exploitation and the exports of fossil ener-…”
supporting
confidence: 92%
“…It appears that promoting renewable energy in some low-income countries may lead to restrain their economic progress in the short run. Inglesi-Lotz and Dogan (2018) suggested that shifting energy consumption away from fossil fuels to renewable energy sources is a challenge for developing countries. Different energy structures between the developing and developed countries are different because of technological and economic conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many scholars conducted in-depth studies on the factors that affect carbon emissions [5][6][7][8]. Many studies show that energy consumption is the main factor affecting carbon emissions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%